Software Users Manual for the Polar Ice Prediction System Version 2.0. - Posey, Pamela G.; Preller, Ruth H.; Crout, Julia W. (1996)
The Polar Ice Prediction System Version 2.0 is an ice-ocean coupled system that provides daily forecasts of ice drift, ice thickness, and ice concentration for most ice-covered areas in the Northern Hemisphere. The model is driven by daily atmospheric forcing from the Navy Operational Global Atmospheric Prediction System. The model is initialized from its own previous 24-h forecast with an additional weak constraint back to Levitus climatology placed on the ocean temperature and salinity. This Software Users Manual (SUM) provides instructions for the operation and use of the PIPS2.0 system. The SUM also includes information concerning the input/output of the system and the necessary commands to execute the forecast system.